Single-molecule FRET measures bends and kinks in DNA - Woźniak, Anna K. (National Academy of Sciences, 2008)
We present advances in the use of single-molecule FRET measurements with flexibly linked dyes to derive full 3D structures of DNA constructs based on absolute distances. The resolution obtained by this single-molecule approach harbours the potential to study in detail also protein- or damage-induced DNA bending. If one is to generate a geometric structural model, distances between fixed positions are needed. These are usually not experimentally accessible because of unknown fluorophore-linker mobility effects that lead to a distribution of FRET efficiencies and distances. To solve this problem, we performed studies on DNA double-helices by systematically varying donor acceptor distances from 2 to 10 nm. Analysis of dye–dye quenching and fluorescence anisotropy measurements reveal slow positional and fast orientational fluorophore dynamics, that results in an isotropic average of the FRET efficiency. We use a nonlinear conversion function based on MD simulations that allows us to include this effect in the calculation of absolute FRET distances. To obtain unique structures, we performed a quantitative statistical analysis for the conformational search in full space based on triangulation, which uses the known helical nucleic acid features. Our higher accuracy allowed the detection of sequence-dependent DNA bending by 16°. For DNA with bulged adenosines, we also quantified the kink angles introduced by the insertion of 1, 3 and 5 bases to be 32° ± 6°, 56° ± 4° and 73 ± 2°, respectively. Moreover, the rotation angles and shifts of the helices were calculated to describe the relative orientation of the two arms in detail.